2023
DOI: 10.3390/ijms24021518
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Osteoprotegerin-Induced Osteoclast Pyroptosis In Vitro

Abstract: Osteoprotegerin (OPG) is a new member of the tumor necrosis factor (TNF) receptor superfamily, which can inhibit the differentiation and activity of osteoclasts by binding to nuclear factor kappa B receptor activator (RANK) competitively with nuclear factor kappa B receptor activator ligand (RANKL). The previous experiments found that OPG can induce apoptosis of mature osteoclasts in vitro, which can inhibit the activity of mature osteoclasts, thereby exerting its role in protecting bone tissue. In addition, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…TREM1, TNFRSF11B and PGF were positively correlated with caspase-1-induced pyroptosis genes (CASP1, NLRP3, PYCARD, IL1B and IL18). Previous studies also reported that these three diagnostic genes increased the expression of NLRP3 and promoted several diseases, such as septic cardiomyopathy via pyroptosis ( 29 , 39 , 43 ). Five pyroptosis-related genes were positively correlated with IL6 and TNF, but negatively correlated with SOX9.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…TREM1, TNFRSF11B and PGF were positively correlated with caspase-1-induced pyroptosis genes (CASP1, NLRP3, PYCARD, IL1B and IL18). Previous studies also reported that these three diagnostic genes increased the expression of NLRP3 and promoted several diseases, such as septic cardiomyopathy via pyroptosis ( 29 , 39 , 43 ). Five pyroptosis-related genes were positively correlated with IL6 and TNF, but negatively correlated with SOX9.…”
Section: Discussionmentioning
confidence: 77%
“…TNFRSF11B, also known as osteoprotegerin (OPG), is a secretory protein that interacts with receptor activator of nuclear factor kappa-B ligand (RANKL) and TNF-related apoptosis-inducing ligand (TRAIL) ( 29 , 30 ). TNFRSF11B was associated with increased expression of NLRP3, caspase 1 and GSDMD, and induced osteoclast pyroptosis to protect the bone tissues ( 29 ). TNFRSF11B plays a significant role in several cardiovascular diseases, including coronary artery syndromes and myocardial infarction ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of murine long bone osteocyte‐Y4 bone cells to fluid shear stress (FSS) led to an increase in OPG expression (Liu, Tang, et al, 2022). OPG not only induced osteoclast apoptosis but also significantly increased the rate of pyroptosis in osteoclastse, which is related to the expression levels of apoptosis‐associated speck‐like protein containing a CARD, pyrin domain‐containing 3 (Pyrin domain containing protein 3 [NLRP3]), caspase‐1, and GSDMD‐N in the classic pyroptosis pathway (Zhu et al, 2023).…”
Section: Mechanical Stress Affects Cell Death In Pdlcsmentioning
confidence: 99%
“…The expression profile of 110+ SASP components secreted by IR-induced senescent OCYs was established in our laboratory previously using a cellular multifactor antibody microarray assay [8,17]. Based on the results of previous experiments, in conjunction with the bioinformatic analysis and literature search, in this study, we focus on the C-C motif chemokine ligand 5 (CCL5), which plays a regulatory role in osteoclastogenesis [18][19][20][21], given the fact that CCL5 promotes the migration of OC precursor cells in a concentration-dependent manner, enhancing osteoclastogenesis. Accordingly, CCL5 can not only stimulate the elevated intracellular Ca 2+ concentrations and prolonged calcium flow, which results in hyperphosphorylation and extensive cellular activation, but it can also activate the JAK1/STAT3 pathway, which is a stressful inflammatory signaling pathway that has the ability to cascade the production and secretion of key SASP factors, especially CCL5, that regulate bone metabolism.…”
Section: Previous Regulatory Interventions For Bone Imbalance Have Mo...mentioning
confidence: 99%